1996
DOI: 10.1046/j.1360-0443.1996.918118710.x
|View full text |Cite
|
Sign up to set email alerts
|

The first hit: circumstances surrounding initiation into injecting

Abstract: Initiation into injecting is a crucial event for continued reproduction of an injecting drug using (IDU) population and for exposure to blood-borne viruses, but little is known about how this happens. Three hundred young injectors were interviewed in Melbourne by peer workers within the first few years of beginning to inject, about the circumstances surrounding their initiation. Most had indications of social disruption, including having left school early, unemployment, family disruption, homelessness and inca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
171
4
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(195 citation statements)
references
References 0 publications
18
171
4
2
Order By: Relevance
“…54 Finally, youths might simply try injection out of curiosity about a drug or the ritual and paraphernalia involved. 12,49,52,55 With respect to tattoos, we can only speculate about the reasons for this association. For example, in some studies, drug users have reported that they would not start to inject because of their fear or dislike of needles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…54 Finally, youths might simply try injection out of curiosity about a drug or the ritual and paraphernalia involved. 12,49,52,55 With respect to tattoos, we can only speculate about the reasons for this association. For example, in some studies, drug users have reported that they would not start to inject because of their fear or dislike of needles.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some studies have shown that women are mostly initiated by a partner or a lover, while men are often initiated by male friends. 49,50,52,[59][60][61] In our study, youths were asked who carried out their first injection. Only 3% of girls and 7% of boys reported that their initiator was a lover; the majority reported that it was a friend or an acquaintance (72% and 60%, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be because first-time injectors typically require assistance, and this is not permitted by most DCRs. Crofts et al (1996) reported that only 12% of IDUs injected themselves the first time; Kermode et al (2007) reported that 94.5% of IDUs in their study were injected by someone else first time. They also found that the majority had helped someone else inject for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear, however, whether a 'most' typical pattern of co-use actually exists, and experimental evidence relating to this issue is scarce (Leri et al, 2003;Benswick et al, 2001; Kidorf and Stitzer, 1993). Furthermore, a pattern of co-use may reflect regional means of drug administration (Diaz et al, 1994;Gossop et al, 2000) determined by nonpharmacological factors such as socioeconomical status (Crofts et al, 1996;Dunn and Laranjeira, 1999), age (Carneiro et al, 1999;Griffiths et al, 1992;Dinwiddie et al, 1996), or gender (Doherty et al, 2000;Benswick et al, 2001). Thus, it is very difficult to study the pharmacological basis of co-use of heroin and cocaine by analyzing patterns of use at the population level.…”
Section: Introductionmentioning
confidence: 99%